Cardiovascular disease and lipids. Issues and evidence for the management of dyslipidaemia in primary care. - Hobbs, F (2003)
The commonest manifestations of cardiovascular disease, namely coronary heart disease (CHD) and stroke, represent the two most common causes of death in the world today. Furthermore, cardiovascular diseases have the highest healthcare utilisation costs in most countries. Both primary and secondary prevention management strategies are essential. Although more than 200 risk factors for CHD have now been identified, the single most powerful predictor of CHD risk is abnormal lipid levels. The relative risk influences of the various lipid sub-fractions are described, with particular emphasis on LDL cholesterol, which represents the principal target for treatment in most management guidelines. Unfortunately, there remains considerable evidence of continued under-management of patients with elevated cholesterol and cardiovascular risk who are eligible for secondary prevention. The barriers contributing to such physician under-performance are numerous. The more recent recognition of the importance of identifying patients at enhanced risk, but without established disease (primary prevention), will require greatly familiarity with the clinical use of CHD risk scoring systems, most of which are based upon the Framingham equation. Special reference is made to groups at particular risk of CHD. In summary, the application of the enormous evidence-base for interventions in cardiovascular disease, especially over the treatment of elevated cholesterol, pose a huge challenge to primary and secondary care in most healthcare systems.